Anion-cation synergistically doped ferric sodium pyrophosphate positive electrode material, preparation method thereof and sodium ion battery

By introducing Q cations and F anions into the positive electrode material of sodium ion battery and forming a carbon coating, the problems of low conductivity and ion diffusion of the positive electrode material of sodium ion battery are solved, and the performance and stability of the material are improved. It is suitable for industrial use Production.

CN119230796APending Publication Date: 2024-12-31GUIZHOU WEIFANG ENERGY NEW MATERIAL TECH CO LTD
View PDF 0 Cites 9 Cited by

Patent Information

Application Number
CN202411584901.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The low electronic conductivity and slow ion diffusion of sodium ion battery positive electrode materials limit the further performance of their performance, resulting in a lag in the development of sodium ion battery positive electrode materials and cannot match the rapid progress of negative electrode materials.

Method used

Using anion-cationic ion-coated sodium ferropyrophosphate positive electrode material, the formation of carbon cladding on the outer surface of the inner core, Q cations and F anions are introduced, the crystal phase structure is optimized, the conductivity and ion diffusion rate are improved, and the specific Preparation method ensures the stability of the material.

Benefits of technology

It significantly improves the conductivity, specific capacity, rate performance and cycle performance of the positive electrode material, enhances the structural stability of the material, is suitable for large-scale industrial production, and has a simple process and high safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230796A_ABST
    Figure CN119230796A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ferric pyrophosphate positive electrode material cooperatively doped with anions and cations, a preparation method of the sodium ferric pyrophosphate positive electrode material and a sodium ion battery, and relates to the field of sodium ion batteries. The anion and cation synergistically doped ferric sodium phosphate pyrophosphate positive electrode material comprises an inner core and a coating layer covering the outer surface of the inner core, the inner core comprises ferric sodium phosphate pyrophosphate, the coating layer comprises carbon, the chemical formula of the ferric sodium phosphate pyrophosphate is Na4-2yFe2.91-xQx (PO4) 2-yP2O7Fy, x is more than 0 and less than or equal to 0.3, and y is more than or equal to 0.03 and less than or equal to 0.08; q comprises at least one of Sn, Ni, Cu, Mg and Mn. The introduced Q positive ions and F negative ions can keep the crystal structure of the body material stable, and the positive ions and the negative ions have a synergistic effect, so that the band gap of the positive electrode material is reduced, the state density near the Fermi level of the positive electrode material is increased, the conductivity of the positive electrode material is enhanced, the specific capacity of the positive electrode material is improved, and the rate and the cycle performance are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and in particular to an anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material, a preparation method thereof, and a sodium ion battery. Background Art

[0002] Given the high abundance of sodium resources in the earth's crust (about 2.64%), their wide distribution and easy access, and the similarities in the working principles of sodium-ion batteries and lithium-ion batteries, sodium-ion batteries have been widely regarded as an ideal alternative to lithium-ion batteries and lead-acid batteries. However, in the development of sodium-ion battery technology, the research and development of electrode materials constitutes a key bottleneck for technological breakthroughs. In recent years, research on negative electrode materials for sodium-ion batteries has made significant progress and is gradually moving towards the threshold of commercial mass production. However, the development of positive electrode materials for sodium-ion batteries is relatively lagging, and research and development efforts still need to be increased to match the rapid progress of negative electrode materials.

[0003] In the process of exploring potential commercial materials, materials such as layered oxides, polyanionic compounds and Prussian blue / white have attracted much attention. Among them, polyanionic compounds have shown great application potential due to their excellent cycle performance and high stability. In particular, iron-based mixed phosphates (Na4Fe3(PO4)2P2O7) and their derivative materials are not only low-cost, but also non-toxic and environmentally friendly, making them the best among polyanionic compounds. However, iron-based mixed phosphate materials have the problems of low electronic conductivity and slow ion diffusion, which limits the further development of their performance. Summary of the invention

[0004] The purpose of the present application is to provide an anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof and a sodium ion battery to solve the above problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A positive electrode material of sodium iron phosphate pyrophosphate co-doped with anions and cations, comprising a core and a coating layer covering the outer surface of the core, wherein the core comprises sodium iron phosphate pyrophosphate, the coating layer comprises carbon, and the chemical formula of the sodium iron phosphate pyrophosphate is Na 4-2y Fe 2.91-x Q x (PO4) 2-y P2O7 y , wherein 0<x≤0.3, 0.03≤y≤0.08; Q includes at least one of Sn, Ni, Cu, Mg, and Mn.

[0007] The present application also provides a method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material as described above, comprising:

[0008] Mixing a sodium source, an iron source, a Q-containing compound, a fluoride, a phosphorus source, a carbon source and a solvent, and vacuum drying to obtain a positive electrode material precursor;

[0009] The positive electrode material precursor is calcined under an inert gas to obtain anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material.

[0010] According to an embodiment of the present application, the mass of the carbon source accounts for 1 to 10% of the mass of the total raw materials, wherein the total raw materials consist of a sodium source, an iron source, a Q-containing compound, a fluoride, a phosphorus source and a carbon source;

[0011] And / or, the mass of the solvent accounts for 1-5% of the mass of the total raw materials.

[0012] According to an embodiment of the present application, the sodium source includes at least one of an organic sodium source, an inorganic sodium source not containing pyrophosphate, and an inorganic sodium source containing pyrophosphate;

[0013] And / or, the iron source comprises an iron-containing compound or a hydrate of an iron-containing compound, and the iron-containing compound comprises at least one of ferrous oxalate, ferrous phosphate, ferrous chloride, ferrous sulfate, and ferrous nitrate;

[0014] And / or, the phosphorus source includes at least one of sodium pyrophosphate, disodium dihydrogen pyrophosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, ferric phosphate, ferrous phosphate, phosphoric acid, and pyrophosphoric acid;

[0015] and / or, the carbon source comprises at least one of citric acid, glucose, sucrose, oxalic acid, polyethylene glycol, ascorbic acid, tartaric acid, maltose, and fructose;

[0016] And / or, the Q-containing compound includes at least one of a Q-containing oxide, a Q-containing oxalate, a Q-containing acetate, and a Q-containing chloride;

[0017] And / or, the fluoride includes at least one of ammonium fluoride, sodium fluoride, potassium fluoride, and boron trifluoride;

[0018] And / or, the solvent includes at least one of ethanol, water, ethylene glycol, and N-methylpyrrolidone.

[0019] According to an embodiment of the present application, when the sodium source includes an organic sodium source, an inorganic sodium source not containing pyrophosphate, and an inorganic sodium source containing pyrophosphate, the molar ratio of the inorganic sodium source not containing pyrophosphate to the organic sodium source and the inorganic sodium source containing pyrophosphate is 1:(1.8-2.2):(1.8-2.2).

[0020] According to an embodiment of the present application, the organic sodium source includes at least one of sodium dihydrogen citrate, trisodium citrate dihydrate, sodium ascorbate, sodium alginate, sodium oleate, disodium tartrate dihydrate, and tetrasodium ethylenediaminetetraacetic acid tetrahydrate;

[0021] The inorganic sodium source not containing pyrophosphate includes at least one of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium chloride, sodium nitrate, sodium acetate, disodium hydrogen phosphate, and sodium dihydrogen phosphate;

[0022] The inorganic sodium source containing pyrophosphate includes at least one of sodium pyrophosphate and disodium dihydrogen pyrophosphate.

[0023] According to an embodiment of the present application, before the vacuum drying, the method further comprises: ball milling the sodium source, the iron source, the Q-containing compound, the fluoride, the phosphorus source, the carbon source and the solvent;

[0024] And / or, the rotation speed of the ball mill is 400-800 r / min, the bead-to-material ratio of the ball mill is (3-10):1, and the ball milling time is 4-15 h.

[0025] According to an embodiment of the present application, the vacuum drying temperature is 80 to 150° C.;

[0026] And / or, the vacuum drying time is 20-60 min.

[0027] According to an embodiment of the present application, the inert gas includes at least one of argon, nitrogen, and helium;

[0028] And / or, the calcination temperature is 400-600°C;

[0029] And / or, the heating rate of the calcination is 2 to 5°C / min;

[0030] And / or, the calcination time is 2 to 12 hours.

[0031] The present application also provides a sodium ion battery, which includes the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material as described above, or includes the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method as described above.

[0032] Compared with the prior art, the beneficial effects of this application include:

[0033] The Q cations and F anions introduced into the positive electrode material of the present application can keep the crystal structure of the bulk material stable, wherein the introduction of the Q cations can optimize the crystal phase and crystal structure, inhibit the phase change reaction process of the NFPP material, stabilize the matrix material, and improve the structural stability of the material, while the fluoride ions have the advantages of strong electronegativity and strong induction effect, which is beneficial to improve the voltage platform of the positive electrode material; the synergistic effect of the anions and cations reduces the band gap of the positive electrode material, increases the state density near the Fermi level of the positive electrode material, enhances the conductivity of the positive electrode material, improves the specific capacity of the positive electrode material, promotes the rate and cycle performance, and improves the conductivity and slow ion diffusion rate of sodium iron phosphate pyrophosphate. Moreover, the positive electrode material of the present application includes a core and a coating layer, and the design of the coating layer avoids direct contact between the core sodium iron phosphate pyrophosphate and the electrolyte, improves the conductivity and stability of the positive electrode material, and is beneficial to improve the rate and cycle stability of the positive electrode material.

[0034] The preparation method of the present application has the advantages of simple process flow, high safety, and controllable cost, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0036] Figure 1 This is the XRD pattern of the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1;

[0037] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1;

[0038] Figure 3 HRTEM image of the positive electrode material prepared in Example 1;

[0039] Figure 4 The anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 of the present application is used in a sodium ion battery, and its first cycle charge and discharge curve under constant temperature of 25°C and 0.2C;

[0040] Figure 5 This is a cycling performance diagram of the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material used in a sodium ion battery at a constant temperature of 25°C and 2C. DETAILED DESCRIPTION

[0041] As used herein:

[0042] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0043] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0044] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0045] In these examples, parts and percentages are by mass unless otherwise indicated.

[0046] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0047] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0048] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0049] A positive electrode material of sodium iron phosphate pyrophosphate co-doped with anions and cations, comprising a core and a coating layer covering the outer surface of the core, wherein the core comprises sodium iron phosphate pyrophosphate, the coating layer comprises carbon, and the chemical formula of the sodium iron phosphate pyrophosphate is Na 4-2y Fe 2.91-x Q x (PO4) 2-y P2O7 y , wherein 0<x≤0.3, 0.03≤y≤0.08; Q includes at least one of Sn, Ni, Cu, Mg, and Mn.

[0050] The present application doped Q cations and F anions into the positive electrode material, and the Q cations and F anions cooperated with each other, which greatly improved the electronic and ionic conductivity of the sodium iron pyrophosphate, and improved the rate performance, specific capacity and cycle performance of the sodium iron pyrophosphate composite material.

[0051] Specifically, the design of the coating layer avoids direct contact between the inner core sodium iron phosphate pyrophosphate and the electrolyte, thereby improving the conductivity and stability of the positive electrode material, and is beneficial to improving the rate and cycle stability of the positive electrode material.

[0052] Illustratively, x can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3 or any value between 0 and 0.3, and y can be 0.03, 0.04, 0.05, 0.06, 0.07, 0.08 or any value between 0.03 and 0.08.

[0053] The present application also provides a method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material as described above, comprising:

[0054] Mixing a sodium source, an iron source, a Q-containing compound, a fluoride, a phosphorus source, a carbon source and a solvent, and vacuum drying to obtain a positive electrode material precursor;

[0055] The positive electrode material precursor is calcined under an inert gas to obtain anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material.

[0056] The positive electrode material prepared by the method has high conductivity and ion diffusion rate, and the positive electrode material has high specific capacity, rate performance and long cycle life. Moreover, the preparation method of the present application also has the advantages of simple process flow, high safety and controllable cost, and is suitable for large-scale industrial production and application.

[0057] According to the embodiments of the present application, the molar ratio of each element in the sodium source, the iron source, the Q-containing compound, the fluoride, and the phosphorus source is the same as that of the sodium ferric pyrophosphate Na4-2y Fe 2.91-x Q x (PO4) 2-y P2O7 y The stoichiometric ratio of each element in the phosphate pyrophosphate Na 4-2y Fe 2.91-x Q x (PO4) 2-y P2O7 y The stoichiometric ratio of each element in the mixture is used to calculate the amount of sodium source, iron source, Q-containing compound, fluoride and phosphorus source added.

[0058] Furthermore, the molar ratio of sodium in the sodium source to iron in the iron source, Q element in the Q-containing compound, fluorine in the fluoride, and phosphorus in the phosphorus source is (4-2y):(2.91-x):x:y:(4-y), and the specific molar ratio is (3.84~3.94):(2.61~2.91):(0~0.3):(0.03~0.08):(3.92~3.97).

[0059] Illustratively, the molar ratio of sodium in the sodium source to iron in the iron source, the Q element in the Q-containing compound, the fluorine in the fluoride, and the phosphorus in the phosphorus source can be 3.94:2.91:0:0.03:3.97, 3.84:2.61:0.3:0.08:3.92, 3.84:2.91:0:0.08:3.92, 3.94:2.61:0.3:0.03:3.97 or any value between (3.84-3.94):(2.61-2.91):(0-0.3):(0.03-0.08):(3.92-3.97).

[0060] According to the embodiments of the present application, the mass of the carbon source accounts for 1 to 10% of the total raw material mass, wherein the total raw material is composed of a sodium source, an iron source, a Q-containing compound, a fluoride, a phosphorus source and a carbon source; when the mass of the carbon source is within the above range, a dense coating layer can be formed on the outer surface of the inner core, which optimizes the outer surface properties of the material, inhibits the direct contact between the inner core sodium iron phosphate pyrophosphate material and the electrolyte, and can effectively improve the conductivity and stability of the material, thereby improving the rate and cycle stability of the material. If the content of the carbon source is too little, the improvement in the conductivity and surface properties of the material will be small, and the electronic transmission effect of the material cannot be well exerted. If the content of the carbon source is too much, the thickness of the coating layer will be too large, which will hinder the transmission speed of sodium ions, reduce the utilization rate of the NFPP main material, reduce the compaction density of the material, and greatly reduce the electrochemical performance of the material.

[0061] Exemplarily, the mass of the carbon source accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 1 and 10% of the total raw material mass.

[0062] And / or, the mass of the solvent accounts for 1 to 5% of the total raw material mass. When the mass of the solvent is within the above range, it can not only play a grinding aid effect, making the ball milling more complete and more uniform, but also effectively inhibit the oxidation of divalent iron ions, provide more active sites, and thus improve the electrochemical properties of the material. If the mass of the solvent is too little, the grinding effect will be poor, and the inhibitory effect on divalent iron ions will not be good; if the mass of the solvent is too much, the later drying time will be too long, increasing energy consumption, and also increasing the cost of using raw materials.

[0063] Exemplarily, the mass of the solvent accounts for 1%, 2%, 3%, 4%, 5% or any value between 1% and 5% of the total raw material mass.

[0064] According to an embodiment of the present application, the sodium source includes at least one of an organic sodium source, an inorganic sodium source not containing pyrophosphate, and an inorganic sodium source containing pyrophosphate;

[0065] Inorganic sodium sources containing pyrophosphate include P2O7 4- , which can inhibit PO4 3- The self-polymerization reaction is beneficial to improving the stability of the positive electrode material.

[0066] The organic sodium source can not only serve as a sodium source, but also provide an in-situ carbon source. Specifically, after high-temperature carbonization, the organic sodium source can be carbonized synchronously during the formation of sodium iron pyrophosphate crystals, and a carbon layer can be formed in situ on the outer surface of the sodium iron pyrophosphate, thereby enhancing the conductivity between the sodium iron pyrophosphate particles and helping to improve the electrochemical performance of the positive electrode material.

[0067] Inorganic sodium sources that do not contain pyrophosphate can provide an additional source of sodium.

[0068] When the sodium source includes an organic sodium source, an inorganic sodium source without pyrophosphate, and an inorganic sodium source with pyrophosphate, the positive electrode material can have better electrochemical performance. Under the synergistic effect of the above three sodium sources, the conductivity of the material can be further improved and the crystal structure of the material can be optimized.

[0069] And / or, the iron source comprises an iron-containing compound or a hydrate of an iron-containing compound, and the iron-containing compound comprises at least one of ferrous oxalate, ferrous phosphate, ferrous chloride, ferrous sulfate, and ferrous nitrate;

[0070] And / or, the phosphorus source includes at least one of sodium pyrophosphate, disodium dihydrogen pyrophosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, ferric phosphate, ferrous phosphate, phosphoric acid, and pyrophosphoric acid;

[0071] And / or, the carbon source includes at least one of citric acid, glucose, sucrose, oxalic acid, polyethylene glycol, ascorbic acid, tartaric acid, maltose, and fructose; these carbon sources can be used to form a coating layer, which can inhibit the direct contact between the inner core sodium iron phosphate pyrophosphate material and the electrolyte, which is beneficial to improving the conductivity and stability of the material, and is beneficial to improving the rate and cycle stability of the positive electrode material.

[0072] And / or, the Q-containing compound includes at least one of a Q-containing oxide, a Q-containing oxalate, a Q-containing acetate, and a Q-containing chloride;

[0073] For example, the Q-containing compound includes tin dioxide, nickel acetate, copper acetate, magnesium acetate, and manganese acetate.

[0074] And / or, the fluoride includes at least one of ammonium fluoride, sodium fluoride, potassium fluoride, and boron trifluoride;

[0075] And / or, the solvent includes at least one of ethanol, water, ethylene glycol, and N-methylpyrrolidone. These solvents can fully disperse the raw materials and improve the uniformity of the materials.

[0076] According to an embodiment of the present application, when the sodium source includes an organic sodium source, an inorganic sodium source not containing pyrophosphate, and an inorganic sodium source containing pyrophosphate, the molar ratio of the inorganic sodium source not containing pyrophosphate to the organic sodium source and the inorganic sodium source containing pyrophosphate is 1:(1.8-2.2):(1.8-2.2). If the content of the inorganic sodium source not containing pyrophosphate is too much, the content of the organic sodium source and the inorganic sodium source containing pyrophosphate will be relatively small. The lack of the organic sodium source will result in a poor carbon coating effect of the material. The lack of the inorganic sodium source containing pyrophosphate will result in a poor carbon coating effect of the material. 4- , increased PO4 3- The self-polymerization reaction reduces the stability of the material. If the content of the organic sodium source is too much, it will lead to excessive in-situ carbon, which will reduce the specific capacity. If the content of the organic sodium source is too little, it will lead to poor in-situ carbon coating effect.

[0077] Exemplarily, the molar ratio of the inorganic sodium source not containing pyrophosphate to the organic sodium source and the inorganic sodium source containing pyrophosphate can be 1:1.8:1.8, 1:1.9:1.9, 1:2:2, 1:2.1:2.1, 1:2.2:2.2 or any value between 1:(1.8-2.2):(1.8-2.2).

[0078] According to an embodiment of the present application, the organic sodium source includes at least one of sodium dihydrogen citrate, trisodium citrate dihydrate, sodium ascorbate, sodium alginate, sodium oleate, disodium tartrate dihydrate, and tetrasodium ethylenediaminetetraacetic acid tetrahydrate;

[0079] The inorganic sodium source not containing pyrophosphate includes at least one of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium chloride, sodium nitrate, sodium acetate, disodium hydrogen phosphate, and sodium dihydrogen phosphate;

[0080] The inorganic sodium source containing pyrophosphate includes at least one of sodium pyrophosphate and disodium dihydrogen pyrophosphate.

[0081] According to an embodiment of the present application, before the vacuum drying, the method further comprises: ball milling the sodium source, the iron source, the Q-containing compound, the fluoride, the phosphorus source, the carbon source and the solvent;

[0082] Furthermore, the ball milling is carried out in a ball mill, and the raw materials can be evenly dispersed by ball milling. Exemplarily, the ball milling can be carried out in a planetary ball mill, and the ball milling container can be any one of an agate ball milling jar, a ceramic ball milling jar, a polytetrafluoroethylene ball milling jar, a corundum ball milling jar, and a zirconia ball milling jar.

[0083] And / or, the rotation speed of the ball mill is 400-800 r / min, the bead-to-material ratio of the ball mill is (3-10):1, and the ball milling time is 4-15 h.

[0084] Illustratively, the rotation speed of the ball mill can be 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min or any value between 400 and 800 r / min, the bead-to-material ratio of the ball mill can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any value between (3 and 10):1, and the ball milling time can be 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or any value between 4 and 15 h.

[0085] According to an embodiment of the present application, the vacuum drying temperature is 80 to 150° C.;

[0086] Illustratively, the vacuum drying temperature may be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or any value between 80 and 150°C.

[0087] And / or, the vacuum drying time is 20-60 min.

[0088] Exemplarily, the vacuum drying time can be 20 min, 30 min, 40 min, 50 min, 60 min or any value between 20-60 min.

[0089] According to an embodiment of the present application, the inert gas includes at least one of argon, nitrogen, and helium;

[0090] And / or, the calcination temperature is 400-600°C;

[0091] For example, the calcination temperature may be 400°C, 450°C, 500°C, 550°C, 600°C or any value between 400 and 600°C.

[0092] And / or, the heating rate of the calcination is 2 to 5°C / min;

[0093] For example, the heating rate of the calcination may be 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min, or any value between 2 and 5° C. / min.

[0094] And / or, the calcination time is 2 to 12 hours.

[0095] Illustratively, the calcination time can be 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or any value between 2 and 12 h.

[0096] Furthermore, before calcination, the method further comprises: grinding the positive electrode material precursor. After calcination, the method further comprises: naturally cooling the calcined product and then grinding and crushing it.

[0097] The present application also provides a sodium ion battery, which includes the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material as described above, or includes the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method as described above.

[0098] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0099] Example 1

[0100] Example 1 provides a sodium iron phosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn0.06 (PO4) 1.95 P2O7 0.05 , and its preparation method comprises the following steps:

[0101] Sodium carbonate, trisodium citrate dihydrate and sodium pyrophosphate (the molar ratio of sodium carbonate to trisodium citrate dihydrate and sodium pyrophosphate is 1:2:2), ferrous oxalate dihydrate, tin dioxide, ammonium dihydrogen phosphate (the phosphorus source consists of sodium pyrophosphate and ammonium dihydrogen phosphate) and ammonium fluoride are weighed according to the molar ratio of Na, Fe, Sn, P and F being 3.9:2.85:0.06:3.95:0.05, and then 5% of citric acid accounting for the total mass of the raw materials is weighed, mixed evenly, and then 2% of anhydrous ethanol accounting for the total mass of the raw materials is added, and the mixture is ball-milled and dispersed at 500r / min in a planetary ball mill for 10 hours, and then vacuum dried at 120°C for 30 minutes to obtain a positive electrode material precursor. The cathode material precursor is then ground, and the ground product is transferred to a high-temperature tube furnace. In an argon atmosphere, the temperature is raised to 500°C at 3°C / min and kept warm for 10 hours. After naturally cooling to room temperature, it is ground and crushed to obtain anion-cation co-doped sodium iron phosphate pyrophosphate cathode material.

[0102] Figure 1 The XRD spectrum of the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1 is shown. The diffraction peaks of the main crystal planes of the positive electrode material prepared in Example 1 are all sharp, and the diffraction peaks of the positive electrode material in Example 1 are highly consistent with the diffraction peaks of the Na4Fe3(PO4)2P2O7 standard PDF card, and there is no obvious impurity diffraction peak, indicating that the positive electrode material prepared in Example 1 contains Na4Fe3(PO4)2P2O7, and the material has high crystallinity and a relatively pure phase. Moreover, the diffraction peak of the positive electrode material in Example 1 is shifted to the right as a whole, that is, the diffraction angle becomes larger. It can be seen from the Bragg equation (d=nλ / 2sinθ) that this is attributed to the radius of the doped anions and cations (F - and Sn 4+ ) are smaller than the original anion and cation radius (PO4 3- and Fe 2+ )(F - (136pm) <PO4 3- (310pm) and Sn 4+ (71pm) <Fe 2+ (76pm)).

[0103] Figure 2Shown is the SEM image of the positive electrode material prepared in Example 1, indicating that the material has a porous property, which is attributed to the simultaneous carbonization of the sodium source and the carbonization decomposition of the carbon source during the nucleation process of the organic sodium source in the sodium iron phosphate pyrophosphate particles, a part of which is in situ attached to the sodium iron phosphate pyrophosphate particles in the inner core, and a small amount of other carbon sources may be accompanied by the carbon source The reduction of a small amount of previously oxidized iron ions produces carbon oxides, which are released from the inner core to produce porous characteristics.

[0104] Figure 3 HRTEM image of the positive electrode material prepared by the sample of Example 1. Figure 3 It can be seen that there is a uniformly distributed carbon coating layer on the surface of the positive electrode material.

[0105] Example 2

[0106] Example 2 provides a sodium iron phosphate pyrophosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn 0.06 (PO4) 1.95 P2O7 0.05 .

[0107] The preparation method of Example 2 is similar to that of Example 1, except that the sodium source in Example 2 is sodium carbonate and trisodium citrate dihydrate, wherein the molar ratio of sodium carbonate to trisodium citrate dihydrate is 1:2, the phosphorus source in Example 2 is diammonium dihydrogen phosphate, and other conditions are consistent with those in Example 1.

[0108] Example 3

[0109] Example 3 provides a sodium iron phosphate pyrophosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn 0.06 (PO4) 1.95 P2O7 0.05 .

[0110] The preparation method of Example 3 is similar to that of Example 1, except that the sodium sources of Example 3 are sodium carbonate and sodium pyrophosphate, wherein the molar ratio of sodium carbonate to sodium pyrophosphate is 2:1, and other conditions are consistent with those of Example 1.

[0111] Example 4

[0112] Example 4 provides a sodium iron phosphate pyrophosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn 0.06 (PO4) 1.95 P2O7 0.05 .

[0113] The preparation method of Example 4 is similar to that of Example 1, except that the sodium sources in Example 4 are sodium pyrophosphate and trisodium citrate dihydrate, wherein the molar ratio of sodium pyrophosphate to trisodium citrate dihydrate is 1:1, and other conditions are consistent with those of Example 1.

[0114] Example 5

[0115] Example 5 provides a sodium iron phosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Ni 0.06 (PO4) 1.95 P2O7 0.05 .

[0116] The preparation method of Example 5 is similar to that of Example 1, except that the doping element Q in Example 5 is Ni, the Q-containing compound in Example 5 is nickel acetate, and other conditions are consistent with those in Example 1.

[0117] Example 6

[0118] Example 6 provides a sodium iron phosphate pyrophosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Cu 0.06 (PO4) 1.95 P2O7 0.05 .

[0119] The preparation method of Example 6 is similar to that of Example 1, except that in Example 6, the doping element Q is Cu, the Q-containing compound is copper acetate, and other conditions are consistent with those of Example 1.

[0120] Example 7

[0121] Example 7 provides a positive electrode material Na of sodium iron phosphate pyrophosphate co-doped with anions and cations 3.9 Fe 2.85 Mg 0.06 (PO4) 1.95 P2O7 0.05 .

[0122] The preparation method of Example 7 is similar to that of Example 1, except that the doping element Q in Example 7 is Mg, the Q-containing compound is magnesium acetate, and other conditions are consistent with those in Example 1.

[0123] Example 8

[0124] Example 8 provides a positive electrode material Na of sodium iron phosphate pyrophosphate co-doped with anions and cations 3.9 Fe 2.85 Mn 0.06 (PO4) 1.95 P2O7 0.05.

[0125] The preparation method of Example 8 is similar to that of Example 1, except that the doping element Q in Example 8 is Mn, the Q-containing compound is manganese acetate, and other conditions are consistent with those in Example 1.

[0126] Example 9

[0127] Example 9 provides a sodium iron phosphate pyrophosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn 0.06 (PO4) 1.95 P2O7 0.05 .

[0128] The preparation method of Example 9 is similar to that of Example 1, except that the sodium source in Example 9 is sodium carbonate, the phosphorus source is diammonium phosphate, and other conditions are consistent with those in Example 1.

[0129] Example 10

[0130] Example 10 provides a sodium iron phosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn 0.06 (PO4) 1.95 P2O7 0.05 .

[0131] The preparation method of Example 10 is similar to that of Example 1, except that the sodium source of Example 10 is sodium pyrophosphate, the phosphorus source is diammonium phosphate, and other conditions are consistent with those of Example 1.

[0132] Embodiment 11

[0133] Example 11 provides a sodium iron phosphate pyrophosphate material Na co-doped with anions and cations 3.9 Fe 2.85 Sn 0.06 (PO4) 1.95 P2O7 0.05 .

[0134] The preparation method of Example 11 is similar to that of Example 1, except that in Example 11, the sodium source is trisodium citrate dihydrate, the phosphorus source is diammonium phosphate, and other conditions are consistent with those of Example 1.

[0135] Comparative Example 1

[0136] Comparative Example 1 provides an anion-doped sodium iron phosphate material Na 3.9 Fe 2.91 (PO4) 1.95 P2O7 0.05 .

[0137] The preparation method of Comparative Example 1 is similar to that of Example 1, except that: in Comparative Example 1, the molar ratio of the Na element (the molar ratio of sodium carbonate, trisodium citrate dihydrate and sodium pyrophosphate is 1:2:2), the Fe element, the P element and the F element is 3.9:2.91:3.95:0.05, and tin dioxide is not added in the preparation method of Comparative Example 1, and other conditions are consistent with those of Example 1.

[0138] Comparative Example 2

[0139] Comparative Example 2 provides a cation-doped sodium iron phosphate material Na4Fe 2.85 Sn 0.06 (PO4)2P2O7.

[0140] The preparation method of Comparative Example 2 is similar to that of Example 1, except that the molar ratio of the Na element (the molar ratio of sodium carbonate, trisodium citrate dihydrate and sodium pyrophosphate is 1:2:2), the Fe element, the Sn element and the P element in Comparative Example 2 is 4:2.85:0.06:4, and ammonium fluoride is not added in the preparation method of Comparative Example 2, and other conditions are consistent with those in Example 1.

[0141] Comparative Example 3

[0142] Comparative Example 3 provides a sodium iron phosphate pyrophosphate material Na4Fe 2.91 (PO4)2P2O7.

[0143] The preparation method of Comparative Example 3 is similar to that of Example 1, except that the molar ratio of the Na element, the Fe element, and the P element in Comparative Example 3 is 4:2.91:4, the sodium source in Comparative Example 3 is sodium carbonate, and neither tin dioxide nor ammonium fluoride is added in the preparation method of Comparative Example 3, and other conditions are consistent with those in Example 1.

[0144] Comparative Example 4

[0145] Comparative Example 4 provides a sodium iron phosphate material Na co-doped with anions and cations. 3.8 Fe 2.85 Sn 0.06 (PO4) 1.9 P2O7 0.1 .

[0146] The preparation method of Comparative Example 4 is similar to that of Example 1, except that the molar ratio of the P element to the F element in Comparative Example 4 is 3.9:0.1, and other conditions are consistent with those in Example 1.

[0147] Comparative Example 5

[0148] Comparative Example 5 provides a sodium iron phosphate material Na co-doped with anions and cations. 3.96 Fe2.85 Sn 0.06 (PO4) 1.98 P2O7 0.02 .

[0149] The preparation method of Comparative Example 5 is similar to that of Example 1, except that the molar ratio of the P element to the F element in Comparative Example 5 is 3.98:0.02, and other conditions are consistent with those in Example 1.

[0150] The positive electrode materials synthesized in the above embodiments and comparative examples were assembled into button-type sodium ion batteries, and the test conditions were: temperature: 25°C; cut-off voltage: 1.5-3.8V; electrolyte: 1M NaPF6+EC / DMC(1 / 1)+5% FEC; test system: Newwell constant temperature test box.

[0151] Figure 4 The positive electrode material of Example 1 is applied to a sodium ion battery, and the first cycle charge and discharge curve of 0.2C (the current density of 1C is 129mAg -1 ),Depend on Figure 4 It can be seen that the charge and discharge platform is around 3V, and its voltage window is relatively wide, reaching 1.5-3.8V. Its first-cycle discharge specific capacity is as high as 109mAh / g, which has a high energy density.

[0152] Figure 5 The positive electrode material of Example 1 is applied to a sodium ion battery, and the cycle performance diagram under 2C conditions (the current density of 1C is 129mAg -1 ),Depend on Figure 5 It can be seen that the cycle retention rate of 100 times at 2C rate is as high as 100.78%, and its first cycle specific capacity can reach 98.40mAh / g, indicating that the positive electrode material has excellent cycle stability and is suitable for application in the field of sodium ion battery energy storage.

[0153] Table 1 below shows the test data of the first discharge specific capacity at 0.2C and 2C of the button-type sodium ion batteries assembled from the positive electrode materials prepared in each embodiment and comparative example, as well as the capacity retention rate after 100 cycles at 2C (the current density at 1C is 129 mAg -1 ).

[0154] Table 1 Summary of electrochemical performance test data of various embodiments and comparative examples

[0155]

[0156]

[0157] It can be seen from Table 1 that the electrochemical performance of the positive electrode materials of Examples 1-11 is significantly better than that of Comparative Examples 1-5.

[0158] Compared with Examples 2-4 and Examples 9-11, the overall performance of the positive electrode material in Example 1 is significantly better than that in Examples 2-4 and Examples 9-11. This is because Example 1 uses three sodium sources, which include an organic sodium source, an inorganic sodium source without pyrophosphate, and an inorganic sodium source with pyrophosphate. Among them, the inorganic sodium source with pyrophosphate directly provides a more stable P2O7 4- , rather than PO4 at high temperatures 3- Self-polymerization transformation of P2O7 4- ; The organic sodium source can not only provide the sodium source, but also promote the formation of in-situ carbon on the outer surface of the NFPP particles, optimizing the structure of the interface between the electrode material and the electrolyte; the inorganic sodium source without pyrophosphate provides the sodium source. The three sodium sources cooperate with each other, which is conducive to the formation of in-situ carbon on the outer surface of the NFPP particles, enhancing the conductivity of the positive electrode material and further improving the electrochemical performance of the positive electrode material.

[0159] The positive electrode material of Comparative Example 1 is not doped with tin cations, and the electrochemical performance of the positive electrode material of Comparative Example 1 is significantly inferior to that of Example 1. The positive electrode material of Comparative Example 2 is not doped with fluoride anions, and the electrochemical performance of the positive electrode material of Comparative Example 2 is significantly inferior to that of Example 1. This shows that doping with tin cations alone or doping with fluoride anions alone cannot effectively improve the electrochemical performance of the positive electrode material.

[0160] In Comparative Example 3, no tin cations and fluoride anions are doped, and no composite sodium source is used in the preparation process. The electrochemical performance of Comparative Example 3 is significantly inferior to that of other comparative examples. This is because the positive electrode material of Comparative Example 3 contains a small amount of Fe vacancy defects. The vacancy defects lead to incomplete crystal structure, and the conductivity is not compensated in time, resulting in poor rate and cycle performance.

[0161] Compared with Example 1, the electrochemical performance of the positive electrode materials of Comparative Examples 4 and 5 is inferior to that of Example 1. This is because the fluorine content in the positive electrode material of Comparative Example 4 is too high, resulting in a distortion of the structure of the positive electrode material. The fluorine content in the positive electrode material of Comparative Example 5 is too low to effectively regulate the crystal structure of the positive electrode material.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0163] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A positive electrode material of sodium iron phosphate pyrophosphate co-doped with anions and cations, characterized in that: The invention comprises a core and a coating layer covering the outer surface of the core, wherein the core comprises sodium ferric pyrophosphate, the coating layer comprises carbon, and the chemical formula of the sodium ferric pyrophosphate is Na 4-2y Fe 2.91-x Q x (PO4) 2-y P2O7 y , wherein 0<x≤0.3, 0.03≤y≤0.08; Q includes at least one of Sn, Ni, Cu, Mg, and Mn.

2. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: include: Mixing a sodium source, an iron source, a Q-containing compound, a fluoride, a phosphorus source, a carbon source and a solvent, and vacuum drying to obtain a positive electrode material precursor; The positive electrode material precursor is calcined under an inert gas to obtain anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material.

3. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The mass of the carbon source accounts for 1-10% of the mass of the total raw materials, wherein the total raw materials consist of a sodium source, an iron source, a Q-containing compound, a fluoride, a phosphorus source and a carbon source; And / or, the mass of the solvent accounts for 1-5% of the mass of the total raw materials.

4. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The sodium source comprises at least one of an organic sodium source, an inorganic sodium source not containing pyrophosphate, and an inorganic sodium source containing pyrophosphate; And / or, the iron source comprises an iron-containing compound or a hydrate of an iron-containing compound, and the iron-containing compound comprises at least one of ferrous oxalate, ferrous phosphate, ferrous chloride, ferrous sulfate, and ferrous nitrate; And / or, the phosphorus source includes at least one of sodium pyrophosphate, disodium dihydrogen pyrophosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, ferric phosphate, ferrous phosphate, phosphoric acid, and pyrophosphoric acid; and / or, the carbon source comprises at least one of citric acid, glucose, sucrose, oxalic acid, polyethylene glycol, ascorbic acid, tartaric acid, maltose, and fructose; And / or, the Q-containing compound includes at least one of a Q-containing oxide, a Q-containing oxalate, a Q-containing acetate, and a Q-containing chloride; And / or, the fluoride includes at least one of ammonium fluoride, sodium fluoride, potassium fluoride, and boron trifluoride; And / or, the solvent includes at least one of ethanol, water, ethylene glycol, and N-methylpyrrolidone.

5. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: When the sodium source includes an organic sodium source, an inorganic sodium source not containing pyrophosphate, and an inorganic sodium source containing pyrophosphate, the molar ratio of the inorganic sodium source not containing pyrophosphate to the organic sodium source and the inorganic sodium source containing pyrophosphate is 1:(1.8-2.2):(1.8-2.2).

6. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: The organic sodium source includes at least one of sodium dihydrogen citrate, trisodium citrate dihydrate, sodium ascorbate, sodium alginate, sodium oleate, disodium tartrate dihydrate, and tetrasodium ethylenediaminetetraacetate tetrahydrate; The inorganic sodium source not containing pyrophosphate includes at least one of sodium carbonate, sodium bicarbonate, sodium sulfate, sodium chloride, sodium nitrate, sodium acetate, disodium hydrogen phosphate, and sodium dihydrogen phosphate; The inorganic sodium source containing pyrophosphate includes at least one of sodium pyrophosphate and disodium dihydrogen pyrophosphate.

7. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: Prior to the vacuum drying, the method further comprises: ball milling the sodium source, the iron source, the Q-containing compound, the fluoride, the phosphorus source, the carbon source and the solvent; And / or, the rotation speed of the ball mill is 400-800 r / min, the bead-to-material ratio of the ball mill is (3-10):1, and the ball milling time is 4-15 h.

8. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The vacuum drying temperature is 80-150°C; And / or, the vacuum drying time is 20-60 min.

9. The method for preparing the anion-cation coordinated doped sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 2 to 8, characterized in that: The inert gas includes at least one of argon, nitrogen and helium; and / or, the calcination temperature is 400-600°C, And / or, the heating rate of the calcination is 2 to 5°C / min; And / or, the calcination time is 2 to 12 hours.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material of claim 1 or the anion-cation co-doped sodium iron phosphate pyrophosphate positive electrode material prepared by any one of the preparation methods of claims 2-9.

Citation Information

Cited By

  • Sodium-ion battery positive electrode active material, preparation method thereof and sodium-ion battery

    CN119994059A

  • Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof, positive electrode plate, electrochemical energy storage device and electric equipment

    CN120072932A

  • Se anion doped ferric sodium pyrophosphate / carbon positive electrode active material and preparation method and application thereof

    CN120709323A

  • Preparation method and application of sodium ion battery positive electrode material

    CN120717431A

  • Tungsten-doped composite positive electrode material, positive electrode plate, sodium ion battery and electric equipment

    CN120998985A